Investigations into the role of Gfi1 proteins in the exocrine pancreas and the intestine in zebrafish embryos - Alshanqiti, Aisha (2024)
Gfi1 is a transcriptional repressor that plays important biological roles in the development and maintenance of different cell types. Gfi1 knock-out mice suffer from a defect in the exocrine pancreas and intestine. Yet, the exact physiological role of Gfi1 in these organs remains unclear. This study chose to explore the role of Gfi1/b in exocrine pancreatic and intestinal cell differentiation in zebrafish during embryonic stage. Zebrafish were chosen as model here because research on mice has shown that Gfi1 knockout mice suffer from severe neutropenia and die a few months after birth. Our gfi1aaqmc551/qmc551 mutant line showed that adult fish were viable and well fertile with no phenotypic abnormalities. However, full-length bulk RNA-sequencing showed that the qmc551 allele is not a null allele in the exocrine pancreas of zebrafish. RNA in situ hybridisation experiments showed that loss of gfi1aa disrupted the normal expression of the amy2al1 gene but not the expression of prss1 or amy2a in acinar cells of zebrafish embryos. Data from single cell RNA sequencing showed that acinar and centroacinar cells express gfi1aa in the exocrine pancreas of zebrafish embryos. Single cell RNA-sequencing and RNA in situ hybridisation experiments showed that the gfi1aa gene is the only member of the Gfi1/b transcription factor family expressed in exocrine pancreatic tissue in zebrafish embryos. β-cells in the endocrine component of the pancreas develop normally in Gfi1 null zebrafish embryos. Intestinal goblet cells were found in null gfi1aasa11633/sa11633 homozygous zebrafish embryos. These data suggested that Gfi1 is not required for early differentiation of acinar and goblet cells in zebrafish at the embryonic stage.